Complementarities of high energy WAXS and Raman spectroscopy measurements to study the crystalline phase orientation in polypropylene blends during tensile test. (2nd December 2015) - Ponçot, M.; Martin, J.; Chaudemanche, S.; Ferry, O.; Schenk, T.; Tinnes, J.P.; Chapron, D.; Royaud, I.; Dahoun, A.; Bourson, P.
Abstract: In situ measurements using simultaneously Raman spectroscopy and high energy wide angles X-rays scattering (HE-WAXS) were carried out during uniaxial tensile tests of different polypropylene blends (neat isotactic polypropylene – iPP, high impact polypropylene – iPP/EPR, and high impact polypropylene filled by 7%wt of μ-talc particles – iPP/EPR + μ-talc) at various strain rates (5.10 −3 s −1, 10 −3 s −1 and 5.10 −4 s −1 ). Tensile tests were performed using the VidéoTraction™ system to determine the true mechanical behavior of materials in a Representative Volume Element (RVE) where microstructural analyses by the both experimental techniques are obtained. Evolutions of the macromolecular chains orientation have been obtained live at the macromolecular and crystalline cell scales. Experimental results show both that over the course of adding charges in the iPP matrix or increasing the true strain rate, this major micromechanism of deformation of semi-crystalline polymers would be less and less important until its complete disappearance in case of iPP/EPR filled by μ-talc particles. Moreover, correlations made between both techniques evidence similar results over a wide range of true strains. However, measurements diverge at lower and higher strains due to singularities of each both techniques which are discussed in terms of experimental protocols and materials microstructure modifications (transient mesophase, volume damage). Finally, the determination of the true intrinsic mechanical behaviors show similar stress hardening slopes for the three studied iPP blends which means that they all present an highly fibrillar microstructure. The differences of macromolecular chains orientation levels between each material is then discussed in terms of analysis volume of both techniques which could be responsible of their lack of accuracy in case of filled polymers. Graphical abstract: Special experimental set up developed to perform simultaneous high energy wide angle X-rays scattering (P07 beamline, PETRA III, DESY synchrotron, Hamburg, Deutschland) and Raman spectroscopy analysis during a mechanical tensile test: 1) Tensile test machine, 2) Dumbbell-shape specimen, 3) Z-motorized stage, 4) Video camera, 5) Raman head of probe, 6) VidéoTraction™ camera, 7) X-rays monochromator. Highlights: We study the micromechanisms of deformation involved during uniaxial stretching of 3 iPP blends at 3 constant strain rates. An innovative set up was developed to perform simultaneous high energy WAXS and Raman spectroscopy during a tensile test. Complementarities and singularities of both techniques to characterize the polymer microstructure are put in evidence. The determined true intrinsic mechanical behaviors of blends enlighten similar fibrillar microstructures. When large volume damage occurs WAXS and Raman are not able to measure the molecular orientation in fibrils.